Primer design for the amplification of the ammonium transporter genes from the uncultured haptophyte algal species symbiotic with the marine nitrogen-fixing cyanobacterium UCYN-A1 - Salas, Krystal; Cabello, Ana M.; Turk-Kubo, Kendra A.; Zehr, Jonathan P.; Cornejo-Castillo, Francisco M. (Frontiers in Microbiology, 2023)
The multiple symbiotic partnerships between closely related species of the haptophyte algae Braarudosphaera bigelowii and the nitrogen-fixing cyanobacteria Candidatus Atelocyanobacterium thalassa (UCYN-A) contribute importantly to the nitrogen and carbon cycles in vast areas of the ocean. The diversity of the eukaryotic 18S rDNA phylogenetic gene marker has helped to identify some of these symbiotic haptophyte species, yet we still lack a genetic marker to assess its diversity at a finer scale. One of such genes is the ammonium transporter (amt) gene, which encodes the protein that might be involved in the uptake of ammonium from UCYN-A in these symbiotic haptophytes. Here, we designed three specific PCR primer sets targeting the amt gene of the haptophyte species (A1-Host) symbiotic with the open ocean UCYN-A1 sublineage, and tested them in samples collected from open ocean and near-shore environments. Regardless of the primer pair used at Station ALOHA, which is where UCYN-A1 is the predominant UCYN-A sublineage, the most abundant amt amplicon sequence variant (ASV) was taxonomically classified as A1-Host. In addition, two out of the three PCR primer sets revealed the existence of closely-related divergent haptophyte amt ASVs (>95% nucleotide identity). These divergent amt ASVs had higher relative abundances than the haptophyte typically associated with UCYN-A1 in the Bering Sea, or co-occurred with the previously identified A1-Host in the Coral Sea, suggesting the presence of new diversity of closely-related A1-Hosts in polar and temperate waters. Therefore, our study reveals an overlooked diversity of haptophytes species with distinct biogeographic distributions partnering with UCYN-A, and provides new primers that will help to gain new knowledge of the UCYN-A/haptophyte symbiosis.